The Elusive Mitochondrial Genomes of Apicomplexa: Where Are We Now? - Berná, Luisa; Rego, Natalia; Francia, María E. (Frontiers in Microbiology, 2021)
Mitochondria are vital organelles of eukaryotic cells, participating in key metabolic pathways such as cellular respiration, thermogenesis, maintenance of cellular redox potential, calcium homeostasis, cell signaling and cell death. The phylum Apicomplexa is entirely composed of obligate intracellular parasites, causing a plethora of severe diseases in humans, wild and domestic animals. These pathogens include the causative agents of malaria, cryptosporidiosis, neosporosis, East Coast fever and toxoplasmosis, among others. The mitochondria in Apicomplexa has been put forward as a promising source of undiscovered drug targets, and it has been validated as the target of atovaquone, a drug currently used in the clinic to counter malaria. Apicomplexans present a single tubular mitochondria that varies widely both in structure and in genomic content across the phylum. The organelle is characterized by massive gene migrations to the nucleus, sequence rearrangements and drastic functional reductions in some species. Recent third generation sequencing studies have reignited an interest for elucidating the extensive diversity displayed by the mitochondrial genomes of apicomplexans and their intriguing genomic features. The underlying mechanisms of gene transcription and translation are also ill-understood. In this review, we present the state of the art on mitochondrial genome structure, composition and organization in the apicomplexan phylum revisiting topological and biochemical information gathered through classical techniques. We contextualize this in light of the genomic insight gained by second and, more recently, third generation sequencing technologies. We discuss the mitochondrial genomic and mechanistic features found in evolutionarily related alveolates, and discuss the common and distinct origins of the apicomplexan mitochondria peculiarities.